Analisis Pengelolaan Keuangan Desa pada Kantor Wali Nagari Halaban Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota - Asma Ul Husna; Khadijah Nurani (Lembaga Yasin AlSys, 2026)
Nagari financial management is an important aspect in realizing transparent and accountable governance that is in accordance with statutory regulations. Although the implementation of village financial management based on Regulation of the Minister of Home Affairs Number 20 of 2018 has been widely examined, studies that specifically integrate the perspective of Islamic financial management into nagari government financial governance remain limited. This study aims to analyze financial management at the Office of the Wali Nagari Halaban, Lareh Sago Halaban Subdistrict, Lima Puluh Kota Regency, based on Regulation of the Minister of Home Affairs Number 20 of 2018 and to review it from the perspective of Islamic financial management. This study used a qualitative approach with a case study design. The informants consisted of the Wali Nagari, Nagari Secretary, Head of Financial Affairs, and nagari officials involved in financial management, who were selected using purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The results show that the financial management of Nagari Halaban has generally been implemented in accordance with the stages of planning, implementation, administration, reporting, and accountability as regulated in Regulation of the Minister of Home Affairs Number 20 of 2018. However, there are still aspects that need to be improved, particularly administrative accuracy and the optimization of information transparency to the community. From the perspective of Islamic financial management, financial management has reflected the principles of trustworthiness, justice, transparency, accountability, deliberation, and public benefit. These findings contribute to the development of studies on nagari financial governance through the integration of regulatory approaches and Islamic values. The conclusion of this study emphasizes the importance of regulatory compliance and the internalization of Islamic principles in improving the quality of nagari financial management. The implications of this study can serve as a reference for nagari governments in strengthening transparency, accountability, and public benefit in public financial governance.